صوفیاء کی سیرت نگاری پر مشتمل توضیحی کتابیات - Abdul Jabbar Qamar (Seerat Studies, 2025)
While scholars and researchers have produced numerous works on the life of the Holy Prophet ﷺ, as well as Sufis also have expressed their profound love and devotion for Muhammad ﷺ through their writings. This paper presents a brief overview of some prominent Sufi authors who have written on the Prophet’s blessed life, Prophetic virtues and their attributes. The present article offers a concise introduction to major works authored by Sufis on the life of the Holy Prophet ﷺ. In particular, it highlights the writings of Syed Muhammad Hashim Thathvi, Qazi Abdul Daim Daim, Syed Abu al-Faiz Qalandar Ali Suhrawardi, Sufi Barkat Ali Ludhianvi, Syed Muhammad Wajeeh al-Sima Irfani, Khawaja Abdul Rahman Choharvi, Sheikh al-Islam Muhammad Anwarullah Qadri Chishti and Baba Irfan-ul-Haq.